Membrane proteins correlated with expression of the polysialic acid capsule in Escherichia coli K1. - Whitfield, C (1985)
Growth of Escherichia coli K1 strains at 15 degrees C results in a defect in the synthesis or assembly of the K1 polysialic acid capsule. Synthesis is reactivated in cells grown at 15 degrees C after upshift to 37 degrees C, and activation requires protein synthesis (Whitfield et al., J. Bacteriol. 159:321-328, 1984). Using this temperature-induced defect, we determined the molecular weights and locations of membrane proteins correlated with the expression of K1 (polysialosyl) capsular antigen. Pulse-labeling experiments demonstrated the presence of 11 proteins whose synthesis was correlated with capsule appearance at the cell surface. Using the differential solubility of inner and outer membranes in the detergent Sarkosyl, we localized five of the proteins in the outer membrane and four in the inner membrane. The subcellular location of two of the proteins was not determined. Five proteins appeared in the membrane simultaneously with the initial expression of the K1 capsule at the cell surface. One of these proteins, a 40,000-dalton protein localized in the outer membrane, was identified as porin protein K, which previously has been shown to be present in the outer membrane of encapsulated E. coli. The possible role of these proteins in the synthesis of the polysialosyl capsule is discussed.